The impact of climate change and climate policy on the Canadian economy - Jim Davies; Jim MacGee; Jacob Wibe (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2011)
We examine the relative benefits of policy aimed at mitigating GHG emissions in Canada and globally. We find that while a carbon tax that holds the stock of global emissions below the 550 ppm level would yield positive net benefits for the world economy, the impact of such a tax on the Canadian economy would be negative. This result is largely driven by our finding that the damages from small increases in temperature are much smaller in Canada than in the rest of the world.
Keywords: 330; Klimaveränderung; Umweltbelastung; Klimapolitik; Makroökonomischer Einfluss; Energiewirtschaft; Kleines-offenes-Land; Weltmodell; Kanada